2019
DOI: 10.2320/matertrans.mf201919
|View full text |Cite
|
Sign up to set email alerts
|

Strain Induced Segregations in Severely Deformed Materials

Abstract: Severely deformed materials intrinsically contain a large density of crystalline defects like dislocations or boundaries. The interactions between solute atoms or impurities with these defects play a key role in the grain refinement mechanisms as they affect dynamic recovery. This short review manuscript focusses on grain boundary segregations resulting from severe plastic deformation. The important contribution of atom probe tomography for the quantitative characterization of such segregations in various meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 79 publications
(117 reference statements)
0
18
0
1
Order By: Relevance
“…Interestingly, the precipitation sequence usually takes a diffe rent type, with the easy nucleation of stable phase without the classical sequence 3 (through formation of Guinier-Preston-Bagarysatsky (GPB) zones [26]). Besides, strain-induced segregations of solute atoms along GBs have been reported in the Al-Cu system [27,28] and other alloys [29]. In addition, three dimensional atom probe tomography (APT) by Sha et al [30] showed that such segregation of Cu and Mg also occurred during aging in an A2024 alloy.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, the precipitation sequence usually takes a diffe rent type, with the easy nucleation of stable phase without the classical sequence 3 (through formation of Guinier-Preston-Bagarysatsky (GPB) zones [26]). Besides, strain-induced segregations of solute atoms along GBs have been reported in the Al-Cu system [27,28] and other alloys [29]. In addition, three dimensional atom probe tomography (APT) by Sha et al [30] showed that such segregation of Cu and Mg also occurred during aging in an A2024 alloy.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, three dimensional atom probe tomography (APT) by Sha et al [30] showed that such segregation of Cu and Mg also occurred during aging in an A2024 alloy. They could efficiently stabilize UFG structures but also contribute to strengthening [29].…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, the original sub-micrometer Ca filaments (dCa < 1m) are greatly elongated with a thickness dCa*  dCa /  of only 5 nm or less. Thus, at larger levels of deformation, Ca filaments are so much elongated that they start to dissolve in the fcc Al matrix as observed in other immiscible systems [31][32][33][34][35][36]. It starts at the HPT disc periphery where the shear strain is larger, and it progressively reaches the whole sample, leading to a progressive decrease and vanishing of Ca peaks on XRD spectra (Fig.…”
Section: Influence Of Calcium On the Deformation Induced Nanoscaled Structurementioning
confidence: 68%
“…The aim of the present work was to investigate both the influence of segregations and of intermetallic phases in a nanostructured Al-Ca alloy. To reach this goal, it was assumed that the co-deformation of fcc Al and fcc Ca phases could lead to mechanical mixing, promote the nanoscaled structure formation and segregation of the minor element (namely Ca) along grain boundaries, as observed in various immiscible systems [31][32][33][34][35][36]. Thus, a bi-metallic composite material made of fcc Al and fcc Ca phases [37] has been processed by High-Pressure Torsion (HPT) at various strains.…”
Section: -Introductionmentioning
confidence: 99%
“…Известно также, что выделение второй фазы в таких материалах может улучшать их механические характеристики [2]. В экспериментах [3][4][5] отмечалось ускоренное выделение второй фазы в УМЗ-материалах, полученных методами интенсивной пластической деформации. Например, в алюминиевом УМЗ-сплаве Al−Zr, полученном методом интенсивной пластической деформации и затем отожженном при температуре 230 • C, наблюдалось значительное количество наноразмерных выделений фазы Al 3 Zr [5].…”
unclassified